SPEECH FUNCTION OF MALE AND FEMALE TEACHERS IN THE CLASSROOM INTERACTION AT SMA NEGERI 1 KISARAN - Ratih Virda Ramayani; Anggraini Thesisia Saragih (Universitas Negeri Medan, 2022)
The research dealt with speech function used by male and female teachers in classroom interaction at SMA Negeri 1 Kisaran. The aims of the study were: (1) to identify the types of speech function used by the male and female teachers in classroom interaction (2) to analyze the way how the speech function used by the male and female teachers. This study used descriptive qualitative design. The participants of the study were one male English teacher and one female English teacher. The data were collected by following instruments: observation and video recording. The findings of this study revealed that: (1) the types of speech functions used by male teacher are statement (48.05% or 259 clauses), questions (19.9% or 107 clauses), offer (1.7% or 9 clauses), and command (12.6% or 68 clauses). Meanwhile, the types of speech functions used by female teacher are statement (28.6%% or 80 clauses), questions (21.4% or 107 clauses), offer (4.01% or 15 clauses), and command (24.6% or 90 clauses). (2) For the realization of speech functions by male and female teachers there are two ways that have been found in realization structure of male and female teachers speech functions named typical clause mood and non- typical clause mood. In typical clause mood, there were found four ways, statement that realized by declarative mood, question realized by interrogative mood, command realized by imperative mood, and initiating minor that realized by minor. Besides that, in non - typical clause mood found there are three ways in realization of mood by male and female teachers, named statement that realized by tagged declarative, offer that realized by declarative, and command that realized by modulated declarative.